1999
DOI: 10.2334/josnusd.41.93
|View full text |Cite
|
Sign up to set email alerts
|

So-called simple bone cyst of the jaw. A family of pseudocysts of diverse nature and etiology.

Abstract: The nature and etiology of so-called simple bone cyst (SBC) are still a subject of debate. Our comprehensive review of the literature suggests that SBC, which appears histologically to be a single entity, has different natures and etiologies, resulting in divergent clinical features. In addition, an interesting case of mandibular SBC in an 11-year-old girl is presented with details of radiographic changes over a 7-year period. Fully documented patient records revealed that this lesion originated in the apical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 68 publications
(9 reference statements)
1
7
0
1
Order By: Relevance
“…9,12,13 These data have enabled some workers to speculate about the nature of gnathic and extra-gnathic SBCs and whether or not they are the same or different entities. [5][6][7] The clinical data from our subject group with solitary SBCs is in general agreement with other previously published case series; that is, SBCs occur in a generally younger age group of patients (mean: 18.2 years in males and 18.8 years in females) and that the male-to-female distribution is 1:1. Previous studies have also mapped the distributions of SBCs to the mandible primarily with few occurrences in the maxilla or away from the tooth-bearing areas of the jaws.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…9,12,13 These data have enabled some workers to speculate about the nature of gnathic and extra-gnathic SBCs and whether or not they are the same or different entities. [5][6][7] The clinical data from our subject group with solitary SBCs is in general agreement with other previously published case series; that is, SBCs occur in a generally younger age group of patients (mean: 18.2 years in males and 18.8 years in females) and that the male-to-female distribution is 1:1. Previous studies have also mapped the distributions of SBCs to the mandible primarily with few occurrences in the maxilla or away from the tooth-bearing areas of the jaws.…”
Section: Discussionsupporting
confidence: 80%
“…In the jaws, SBCs may contain nothing at all. 6 From a treatment standpoint, SBCs may be monitored without intervention or they can be entered surgically, curetted and closed. Fenestration of the bone surface and packing of the cavity with materials such as GelfoamH gelatin sponge (Pfizer, New York, NY) or gauze has also been performed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, the authors reported male as the most affected by SBC and no gender predilection for ABC (8-11). However, this study showed a higher prevalence of female for both bone entities.…”
Section: Discussionmentioning
confidence: 85%
“…Cysts of the jaws are pathologic cavities within the bone of the maxilla or the mandible, lined by odontogenic epithelium (odontogenic cysts) [5][6][7].…”
Section: Discussionmentioning
confidence: 99%